Crafting a Progressive Legal Landscape of Apostasy in Islamic Criminal Law Reform - Haq, Islamul; Waeno, Muhamadaree; Marlina, Andi; Rasna (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aimed to examine the intricate process of reforming Islamic criminal law to establish a progressive legal system and ensure justice. An empirical approach was adopted with a specific emphasis on abolishing the penalty for apostasy. This qualitative study included in-depth interviews with members of the Fatwa Commission, lecturers, and students to explore viewpoints on crafting the reform of Islamic criminal law and abolishing the punishment for apostasy. Recent results of contemporary studies recommended the revision of Islamic criminal law to abolish the death penalty for apostasy. This perspective showed an effort to ensure consistency between Islamic legal concepts, universal human ideals, and evolving societal settings. This article contributes to the ongoing discourse on reforming Islamic criminal law, shedding light on the complexities involved and advocating for a more humane approach, particularly regarding apostasy. This research, it seeks to bridge the gap between theoretical discussions and practical implications, fostering a deeper understanding of the necessity for reform within Islamic jurisprudence. Through collaboration with stakeholders and continued academic inquiry, it is hoped that these efforts will pave the way for a legal framework that not only respects Islamic principles but also upholds universal human rights standards.